2021
DOI: 10.1002/jat.4274
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of soap and water‐based skin decontamination using in vitro animal models: A systematic review

Abstract: Water and/or soap and water solutions have historically been used as first-line decontamination strategies for a wide variety of dermal contaminants from workplace exposure, environmental pesticides, and civilian chemical warfare. Although water and/or soap and water solutions are often considered a gold standard of decontamination, many studies have found other decontamination methods to be superior. This systematic review summarizes the available data on in vitro animal models contaminated with a various che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…Though soap and water is a widely accepted option, it is not a universal decontaminant. In fact, recent systematic reviews have generally concluded that soap and/or water methods often result in incomplete decontamination (Burli et al, 2021;Chiang et al, 2021aChiang et al, , 2021bGreen et al, 2021). This may be partially attributable to the "wash-in" effect, which is when wet decontamination actually enhances the percutaneous penetration of the contaminant (Moody & Maibach, 2006).…”
mentioning
confidence: 99%
“…Though soap and water is a widely accepted option, it is not a universal decontaminant. In fact, recent systematic reviews have generally concluded that soap and/or water methods often result in incomplete decontamination (Burli et al, 2021;Chiang et al, 2021aChiang et al, , 2021bGreen et al, 2021). This may be partially attributable to the "wash-in" effect, which is when wet decontamination actually enhances the percutaneous penetration of the contaminant (Moody & Maibach, 2006).…”
mentioning
confidence: 99%